Effect of Physicochemical Process Variables on Natural Indigo Dye Production from Strobilanthes cusia Leaves by Response Surface Methodology - Wachid Siti Fatimah; Taranipa Marfitania; Edia Rahayuningsih; Mukmin Sapto Pamungkas (Indonesian Journal of Chemistry, 2022)
The recovery process of indigoid compounds involves enzymatic hydrolysis of indigo precursors continued by oxidation reaction to synthesize indigo pigment. The purpose of this research was to evaluate the effect of physicochemical process variables, i.e., temperature, time, and pH aeration, on indigo yield from Strobilanthes cusia leaves. Small leaf pieces were immersed in distilled water and heated at temperatures (40, 50, and 60 °C) and duration (1, 2, and 3 h). The extract was aerated at different pHs (8, 10, and 12) to form the indigo product. The indigo concentration was quantified through a visible spectrophotometer and high-performance liquid chromatography (HPLC). The optimized condition for indigo production was studied using response surface methodology (RSM). Temperature, time, and interaction between temperature and time significantly affected the indigo yield. The optimized conditions for extraction of indigo dyes were determined to be at 60 °C for 1 h and pH 8 for maximizing the indigo yield. On that condition, the indigo concentration quantified by HPLC was 1.15% (w/v) which was lower than that by the spectrophotometry. By spectrophotometric analysis, the actual indigo content of 1.68% (w/v) on that optimum condition was close to the predicted indigo content of 1.77% (w/v) using RSM.